Drug comparison and categorizing regarded with human serum albumin from years 2006 to 2012 - Shahani, Minoo; Vaseghi Maghvan, Padina; Tadayon, Roya; Rostami, Amin; Ramandi, Marzie; Mohammadian, Taher; Mohammadian, Taher (Archives of Advances in Biosciences, 2013)
Human serum albumin (HSA) is the most abundant protein constituent of blood plasma. This protein consists of a single polypeptide chain of 585 amino acid residues, which has many important physiological functions. HSA can bind and carry many drugs, including anticoagulants, tranquilizers, and general Anesthetics. Some technique such as: fluorescence spectroscopy, three-dimensional fluorescence, UV–visible, FT-IR, circular dichroism (CD), X-ray scattering (SAXS) technique and molecular modeling was utilized to investigate the effects of acceptor on conformation of the donor (HSA). The binding site number n and apparent binding constant KA drugs corresponding thermodynamic parameters, the free energy change (∆G), enthalpy change (∆H), and entropy change (∆S) were calculated. The hydrophobic effect, van der Waals forces, hydrogen bond and electrostatic interactions play a major role in stabilizing the complex. More investigation also revealed that these drugs bind to the amino acids on the hydrophobic pocket of HSA and induce changes to the secondary structure of the HSA. In this study for better understanding of HSA-drug interactions, we categorized drugs into ten groups from years 2006 to 2012 and are suggested that two important parameters such as ΔG0H20 and [D] 1/2 can be calculated for each groups and refer to ten categories to finally indicate that fine structural change in human serum albumin.